2010
DOI: 10.1186/1475-2840-9-65
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations in vascular contractility associated to changes in fatty acid composition and oxidative stress markers in perivascular adipose tissue

Abstract: AimTo test the early effect of fructose-induced changes in fatty acid composition and oxidative stress markers in perivascular adipose tissue (PVAT) upon vascular contractility.MethodsAdult male Wistar rats were fed a commercial diet without (CD) or with 10% fructose (FRD) in the drinking water for 3 weeks. We measured plasma metabolic parameters, lipid composition and oxidative stress markers in aortic PVAT. Vascular contractility was measured in aortic rings sequentially, stimulated with serotonin (5-HT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
(68 reference statements)
1
26
1
4
Order By: Relevance
“…A second possibility is that the fatty acid species released by BAT and PVAT may also afford an anti-inflammatory effect. The ratio of saturated to polyunsaturated fatty acids has been shown to increase in the VAT and abdominal PVAT of high-fructose fed rats (34). Thus under these conditions WAT may release relatively higher levels of saturated fatty acids, which may be more active in stimulating macrophage chemotaxis (23, 37).…”
Section: Discussionmentioning
confidence: 97%
“…A second possibility is that the fatty acid species released by BAT and PVAT may also afford an anti-inflammatory effect. The ratio of saturated to polyunsaturated fatty acids has been shown to increase in the VAT and abdominal PVAT of high-fructose fed rats (34). Thus under these conditions WAT may release relatively higher levels of saturated fatty acids, which may be more active in stimulating macrophage chemotaxis (23, 37).…”
Section: Discussionmentioning
confidence: 97%
“…By creating a VSMC-adipocyte co-culture, these authors demonstrated a decrease in AMPK phosphorylation and an increase in mTOR phosphorylation in VSMCs co-cultured with adipocytes from HFD treated rats (71). Finally, the role of fatty acid (FA) composition was highlighted in a recent article of fructose-fed rat model of metabolic syndrome, in which the PVAT anticontractile effect was diminished in aorta and the ratio of saturated to mono or polyunsaturated FA was increased, antioxidant enzyme expression was decreased and markers of oxidative stress were increased in PVAT (76). In another study, the increased norepinephrine-induced contraction in fructose-fed rats was corrected with losartan in both the presence and absence of PVAT(77).…”
Section: Obesity Insulin Resistance Diabetesmentioning
confidence: 99%
“…In spontaneously hypertensive rats [126] and insulin-resistant fructose-fed rats [127], the relaxing effect of PVAT on mesenteric arteries was found to be impaired. At present, the nature of the ADRFs is not fully clear, although angiotensin 1–7 [115], adiponectin [25••], and hydrogen sulfide [128] have been mentioned as ADRFs.…”
Section: Perivascular Adipose Tissue As a Regulator Of Microvascular mentioning
confidence: 99%